The role of FoxO3a in the pathogenesis of osteoarthritis and its therapeutic applications - Wu, Zhimin; Wang, Xiaofei; Yang, Yuxia; Xia, Cunyi; Lou, Linbing; Fei, Wenyong; Wang, Jingcheng; Dai, Jihang (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a chronic degenerative joint disease predominantly observed in middle-aged and elderly individuals, with its complex pathological mechanisms significantly affecting patients’ quality of life. Due to the absence of effective treatment strategies, there has been a growing emphasis on molecular targeted therapies for OA. As a critical transcription factor, Forkhead box O3a (FoxO3a) plays a vital role in physiological processes such as cell differentiation, survival, and apoptosis. The activity of FoxO3a is modulated by post-translational modifications, including phosphorylation and acetylation, as well as by various signaling pathways. Recent studies have demonstrated that FoxO3a significantly influences the onset and progression of OA by regulating multiple processes in chondrocytes, including redox homeostasis, inflammatory response, cell survival, and matrix degradation. Its active expression presents potential value for the prevention and treatment of OA. This article reviews the research advancements regarding the role of FoxO3a in the pathogenesis of OA, emphasizing its effects on physiological activities such as oxidative stress and regulatory mechanisms in chondrocytes, with the aim of refining the understanding of OA pathogenesis and providing new insights for its prevention and treatment.